PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN BEPIKIR KRITIS MATEMATIS SISWA KELAS VIII SMP - Nainggolan, Cindera Indah Afriana; Purba, Gloria Indira Diana (MES: Journal of Mathematics Education and Science, 2024)
This study aims to improve students' mathematical critical thinking skills through the application of contextual learning models assisted by Geogebra. This type of research is class action research. The subjects of this research were 30 students of Class VIII-3 SMP Negeri 27 Medan. The subject of this research is critical thinking skills using contextual teaching and learning model with Geogebra assisted for two variable linear equation system. This research consisted of two cycles and at the end of each cycle a critical thinking skills test was given. Based on the results of data analysis after taking action in Cycle I by giving a mathematical critical thinking test, it is known that 36.67% have reached the success target. After taking action in Cycle II through a test of students' mathematical critical thinking skills, it was found that 90% had met the success target. The increase was also shown by the average student score from 42.40 to 66.18 in cycle I and increased to 83.96 in cycle II.